Chapter 5: Family policy support for the earner-carer and traditional-family models in Lithuania and Sweden (Edward Elgar Publishing, 2021)
Family policies influence how men and women structure their time in the labour market and in the home. However, analyses based on expenditure data, regime types and single policies, cannot represent how policies support individuals' labour market attachment and care for children. We explore harmonised data on social policies over time to describe how policies support earner-carer and traditional family models in Lithuania and Sweden. We use these cases to describe how measures of earner-carer and traditional-family support have been constructed and compare the policy developments over time. We highlight areas of convergence and divergence in family policy in these two countries with very different histories.